Monolithic dual-wedge prism-based spectroscopic single-molecule localization microscopy - Song Ki-Hee; Brenner Benjamin; Yeo Wei-Hong; Kweon Junghun; Cai Zhen; Zhang Yang; Lee Youngseop; Yang Xusan; Sun Cheng; Zhang Hao F. (Nanophotonics)
By manipulating the spectral dispersion of detected photons, spectroscopic single-molecule localization microscopy (sSMLM) permits concurrent high-throughput single-molecular spectroscopic analysis and imaging. Despite its promising potential, using discrete optical components and managing the delicate balance between spectral dispersion and spatial localization compromise its performance, including nonuniform spectral dispersion, high transmission loss of grating, high optical alignment demands, and reduced precision. We designed a dual-wedge prism (DWP)-based monolithic imaging spectrometer to overcome these challenges. We optimized the DWP for spectrally dispersing focused beam without deviation and with minimal wavefront error. We integrated all components into a compact assembly, minimizing total transmission loss and significantly reducing optical alignment requirements. We show the feasibility of DWP using ray-tracing and numerical simulations. We validated our numerical simulations by experimentally imaging individual nanospheres and confirmed that DWP-sSMLM achieved much improved spatial and spectral precisions of grating-based sSMLM. We also demonstrated DWP-sSMLM in 3D multi-color imaging of cells.